PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA, KOMPETENSI, DAN MOTIVASI TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN KABUPATEN BANYUMAS - Widia Sari; Fatmah Bagis (JURNAL ILMIAH EDUNOMIKA, 2024)
The education office is a public institution that plays a role in providing community services so that the employees involved must work optimally and have good performance. This study aims to analyze the effect of organizational culture, work environment, competence and motivation on employee performance at the Banyumas Regency Education Office. Quantitative methods were used in this study and the sampling technique used saturated samples so that the entire population became respondents. The questionnaire used for analysis was 132 questionnaires, then processed using SPSS. The results showed that organizational culture, work environment and competence partially had a positive and significant effect on employee performance, but motivation partially had no effect on the performance of employees of the Banyumas Regency Education Office. The results of this study are expected to be used as an evaluation of the performance of Banyumas Regency Education Office employees. Keywords: Culture, Environment, Competence, Motivation, Performance